An assessment of the relationship between sustainability reporting and firm profitability of publicly listed companies in the Philippines - Angue, Krischelle Marie M.; Castillo, Gianne Ina D.; Epetia, Ma. Christina (Quezon City School of Economics, University of the Philippines Diliman, 2019)
This study aims to examine the impact of sustainability reporting on firm profitability in the Philippines. Multiple linear regression analysis was used to analyze the data of 194 publicly-listed companies (PLCs) that have submitted sustainability reports in the Philippine Stock Exchange (PSE). In this study, firm profitability is the dependent variable, and it was measured by net profit margin (NPM), return on assets (ROA) and return on equity (ROE). Meanwhile, sustainability reporting is the independent variable. The results reveal a statistically significant and negative
relationship between sustainability reporting and firm profitability (through net profit margin and return on assets) in the short term. No significant relationship is found between sustainability reporting and return on equity. The results imply that it is not profitable for a PLC to publish sustainability reports.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Corporate profits -- Philippines